2023
DOI: 10.3390/v15071484
|View full text |Cite
|
Sign up to set email alerts
|

New Bacteriophages with Podoviridal Morphotypes Active against Yersinia pestis: Characterization and Application Potential

Tamar Suladze,
Ekaterine Jaiani,
Marina Darsavelidze
et al.

Abstract: Phages of highly pathogenic bacteria represent an area of growing interest for bacterial detection and identification and subspecies typing, as well as for phage therapy and environmental decontamination. Eight new phages—YpEc56, YpEc56D, YpEc57, YpEe58, YpEc1, YpEc2, YpEc11, and YpYeO9—expressing lytic activity towards Yersinia pestis revealed a virion morphology consistent with the Podoviridae morphotype. These phages lyse all 68 strains from 2 different sets of Y. pestis isolates, thus limiting their potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Many phages can lyse Y. pestis, including lytic phages previously called Podoviridae phages (such as Pokrovskaya [40], A1122 [41], and Yep-phi [42]), as well as eight recently reported new phages with Podoviridae characteristics (YpEc56, YpEc56D, YpEc57, YpEe58, YpEc1, YpEc2, YpEc11, and YpYeO9) [43]. Because several such phages have specific lytic effects on Y. pestis, some are routinely used for the diagnosis of this disease.…”
Section: Nomenclature Of Y Pestis Phagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many phages can lyse Y. pestis, including lytic phages previously called Podoviridae phages (such as Pokrovskaya [40], A1122 [41], and Yep-phi [42]), as well as eight recently reported new phages with Podoviridae characteristics (YpEc56, YpEc56D, YpEc57, YpEe58, YpEc1, YpEc2, YpEc11, and YpYeO9) [43]. Because several such phages have specific lytic effects on Y. pestis, some are routinely used for the diagnosis of this disease.…”
Section: Nomenclature Of Y Pestis Phagesmentioning
confidence: 99%
“…This consistency was not only observed in terms of genomic arrangement (99-100%), but also in high homology to conserved structural genes. One interesting phenomenon is that when the apl and cI genes were compared, the phage GCS667 clustered apart from other Eganvirus phages, and instead GCS667 clustered with the phages Many phages can lyse Y. pestis, including lytic phages previously called Podoviridae phages (such as Pokrovskaya [40], A1122 [41], and Yep-phi [42]), as well as eight recently reported new phages with Podoviridae characteristics (YpEc56, YpEc56D, YpEc57, YpEe58, YpEc1, YpEc2, YpEc11, and YpYeO9) [43]. Because several such phages have specific lytic effects on Y. pestis, some are routinely used for the diagnosis of this disease.…”
Section: Diversity Of Phages From the Genus Eganvirusmentioning
confidence: 99%
“…Several previous studies have shown in vitro phage efficacy against Y. pestis (2224); however, a few studies have demonstrated in vivo efficacy (25, 26). In one study, phage treatment was shown to delay progression of pneumonic plague; however, all mice still succumbed unless antibiotic therapy was co-administered (26).…”
Section: Introductionmentioning
confidence: 99%